Experimental studies on cement stabilized masonry blocks prepared from brick powder, fine recycled concrete aggregate and pozzolanic materials. (March 2017) - Kumar, B.M. Vinay; Ananthan, H.; Balaji, K.V.A.
Abstract: This experimental work deals with the assessment of strength and water absorption characteristics of cement stabilized masonry block (CSMB) units made with brick powder (BP) and fine recycled concrete aggregate (FRCA) along with pozzolanic materials such as silica fume (SF), fly ash (FA) and ground granulated blast furnace slag (GGBS) as partial replacement for cement. The basic tests such as, dry density, 28 days wet compressive strength, water absorption and rate of moisture absorption are performed on CSMB units of size 190×90×90 mm. The correction factors that are available in the literature, with respect to fired clay bricks and compressed earth blocks, so as to account for the confinement of specimens by platen restraints at the ends are used to assess the uniaxial strength of CSMB units. The corrected average values of wet compressive strength of CSMB units at 28 days are found to meet the minimum requirement of 3.5 MPa. The percentage of water absorption is found to be higher, but, still within permissible limit of 18% by weight. The average dry density is also found to meet the minimum requirement of 1750 kg/m 3 . The rate of moisture absorption with time is found to follow an exponential trend. Highlights: ● CSMB units are prepared with 94% recycled materials. ● The 28 days wet compressive strength meets the minimum requirement of 3.5 MPa. ● The percentage of water absorption is found to be within 18% by weight. ● The average dry density is found to meet the minimum requirement of 1750 kg/m 3 .